What sort of novel is The Wire? Voice, dialogue and protest. Issue 3 (1st September 2015) - Stacy, Ivan
This article responds to the numerous comparisons between The Wire and realist or naturalist novels. It argues that The Wire's mimetic qualities depict many of the problems facing Baltimore and, by extension, neo-liberal America. However, it argues that the show does not just articulate complaints, but also proposes solutions, and that these solutions can be identified through two other concepts associated with the novel: polyphony and minor literature. The article uses Mikhail Bakhtin's concept of polyphony to examine that way that different voices compete and interact in the series, but notes that, where the relationship between discourses remains conflictual, long-lasting or fundamental change remains unlikely. The article suggests that where more significant change does take place is through the creation of the collective voices associated with Gilles Deleuze and Félix Guattari's concept of minor literature.